2008
DOI: 10.1016/j.ambp.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Overweight and Ankle Injuries in Children

Abstract: OBJECTIVES-Overweight children are at increased risk for many medical problems. Trauma is the leading etiology of childhood morbidity and mortality. No previous study has evaluated the association between overweight and acute ankle injuries in children. We hypothesized that being overweight is associated with an increased risk of ankle injury in children.METHODS-We conducted a case-control study in an urban pediatric emergency department. Subjects aged 5 to 19 years were recruited from June 2005 through July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 17 publications
0
23
0
3
Order By: Relevance
“…That study did not, however, assess the association between BMI and the specific fracture locations in the lower extremities. Lower extremity fractures account for between 15% and 22% of long bone fractures in large-scale studies of pediatric fractures [5,21,22,41].…”
Section: Introductionmentioning
confidence: 99%
“…That study did not, however, assess the association between BMI and the specific fracture locations in the lower extremities. Lower extremity fractures account for between 15% and 22% of long bone fractures in large-scale studies of pediatric fractures [5,21,22,41].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Some studies have identified an increased risk of injury among young overweight and obese groups of people. 6,7 Other research, from cross-sectional studies, has shown that increased body weight is associated with an increased risk of unintentional injury 8,9 and with workplace traumatic injury. 10,11 Past studies that have investigated the relationship between obesity and injury have been limited to mostly western populations, by the use of a specific subgroup of persons, or by the use of a cross-sectional study approach.…”
Section: Introductionmentioning
confidence: 99%
“…Klenerman (28) e Zonfrillo et al (29) atentam ainda ao fato de que as crianças podem ser mais facilmente lesionadas durante atividades esportivas do que indivíduos com maturação esquelética completa, pois seus ossos são mais porosos e frágeis, por causa das epífises de crescimento. Dessa forma, Calvete (11) complementa que, no exercício físico desenvolvido para jovens obesos, é importante considerar o peso corporal desses indivíduos como uma sobrecarga durante o esforço físico.…”
Section: Resultsunclassified